Paleoambientes holocênicos da planície do alto Tibagi, Campos Gerais, Sudeste do Estado do Paraná - Guerreiro, Renato Lada (2011)
Variations or climatic and environmental changes in the recent past, are essential to determine with greater certainty of future climate conditions. Within this context, the Campos Gerais region is regarded as an enclave Pleistocene paleoclimate in Parana State, composed of a phytogeographical mosaic of grassland and forests. The current landscape, with natural grassland interspersed with clumps of Araucaria forest and impressive Araucaria is portrayed since the XVIII century. To many researchers, the steppes were Parana's panorama during the ice age. Climate change post-glacial period, with more humid and hot trands led the advances of forests above the plateaus giving rise to the modern floristic coating of Parana State. Some areas, however, still preserve natural fields arousing the interest of those who dedicate themselves to palaeoenvironmental studies of the Quaternary. The occur of peaty sediments in alto Tibagi alluvial plain, enabled proxy records accumulation and conservation, like polen and continental sponge spicules, preserving importants records about Holocene paleoenvironments of the region. The deposition of these sediments occurred with Tibagi river bottom level about 2 to 4 meters higher than today. Based on the extent and thickness of peat, it is estimated that come to paleomass of 14.000.000m³. Currently, the reworking of earlier deposits in drainages, it is estimated that the bog has 10.000.000m³. Palynological data combined with isotopic analysis (13C) and 14C datings testified to the occurrence of tropical environments in the high plains and Tibagi, Campos Gerais in this portion, between 3.220 years BP, at least 1.340 years BP. The registers sugest that the region was covered with natural grasslands and arboreal vegetation affinities with tropical botanical characteristics of the Alto Tibagi plains. It is likely that the current tree cover, composed by Araucaria forest has become established in the study area in recent centuries, after 1.340 years AP., after the end of deposition of peat and deposit slot.